Teaching culture in Colombia bilingüe: from theory to practice - Fandiño Parra, Yamith José (Colombian Applied Linguistics Journal, 2014)
The main topic of this paper is concerned with the incorporation of culture into the teaching of English as a foreign language (EFL) within the context of Colombia Bilingüe. More specifically, some consideration will be given to what culture is, how it can be taught, and what Colombian authors have pointed out in terms of the difficulties and complexities of working with culture in the EFL classroom. It will be suggested that teaching culture is not synonymous with promoting English sociocultural domination or adapting ethnocentric practices, but mainly approaching and reflecting upon one’s and others’ beliefs, attitudes, and behaviors which are intertwined with language itself. The main premise of the paper is that effective teaching of culture can be achieved if the Colombian EFL community strives to construct a coherent discourse that allows developing teaching models and learning experiences within the theoretical framework of the postmethod condition, world Englishes, and critical multiculturalism. Ultimately, such discourse can encourage Colombian EFL teachers to explore and implement five teaching strategies to engage learners in experiences designed to help them interact successfully with people with different cultural backgrounds.